(untitled) (Research, Society and Development, 2020)
In the present study, buffalo milk caseinate hydrolysates produced by bromelain, neutrase, papain and trypsin were ultra-filtered and different fractions were assessed for antioxidant, inhibition of angiotensin converting enzyme and antimicrobial activity. Biological potential was assessed by a number of metrics: ability to remove radicals of 2,2’-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid), 2,2’-diphenyl-1-picrylhydrazyl (DPPH) and hydroxyls; copper and iron chelation; antidiabetic properties; antihypertensive assay; and antibacterial activity against Escherichia coli ATCC 25922, Listeria monocytogenes ATCC 19114, Salmonella typhimurium ATCC 14028 and Staphylococcus aureus ATCC 25923 strains. The tests for scavenging of hydroxyl radicals and DPPH revealed a greater potential in the 3–10 kDa fractions. Iron chelation activity >70% was observed in all the fractions, including <3 kDa. Copper chelation was >60% in fractions >10 kDa. α-Amylase inhibition and antihypertensive activity was optimal in the <3 kDa fraction. Antibacterial activity ranged between 3.28 and 100% inhibition against microorganisms tested, the fraction <3 kDa showed a greater inhibitory potential. The antihypertensive activity of fractions ranged between 39.35 and 89.58%. All treatments were able to produce hydrolysates and fractions with biological potential and, so the ultrafiltration method proved to be effective in the separation of peptides with different molar masses and potential use in the food or pharmaceutical industry.